Analisis Sistem Pengendalian Intern atas Penerimaan Kas pada PT Bank Sumut - Aritonang, Berliana; Samosir, Hendrik E. S.; Hutapea, Herti Diana (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
PT Bank Sumut is a BUMD company in Indonesia which operates in the business sector of banking services and financial services products. PT Bank Sumut functions as a driver of the pace of development in the region and acts as a regional cash holder by carrying out business activities as a commercial bank. Cash is an asset that is very easily transferable and ownership cannot be proven. Therefore, it is necessary to have a cash control system that aims to control all company activities. This research aims to analyze and find out whether the internal control elements for cash receipts that have been determined are in accordance with those carried out by PT Bank Sumut. The type of data used in this research is document data and the data source is primary data. The data collection techniques used are interview and documentation techniques. And the analysis technique used in this research is descriptive and comparative, namely an analysis method by first collecting, classifying and interpreting data so that it can provide a clear picture of the problem being studied, then comparing the results with their application.